(untitled) (International Journal of Environmental Sciences, 2025)
Pregnancy is a pivotal aspects of many women’s lives, symbolizing hope, joy and new beginnings. However infertility has become increasingly prevalent, affecting a significant portion of population. In India on an average 10-15% of couple having infertility issues. There are lost of reasons causing infertility fallopian tubal block is one among them. The fallopian tube play a significant role in reproduction, allowing sperm to fertilize the egg and transfer conceptus from ampullary part to uterine cavity. One or both fallopian tubes are blocked preventing the egg fertilization and transfer the embryo for implantation are consider under Tubal blockage. Uttar basti is an Ayurvedic procedure that involves introducing medicated oil into uterine cavity to potentially clear tubal blockages. It is minimally invasive approach offer a valuable alternative to conventional treatments for tubal blockage related infertility.